PHENOL WASTE TREATMENT USING OZONE-PLASMA HYBRID REACTOR. Issue 1 (February 2021) - Luvita, Veny; Bismo, Setijo; Sugiarto, Anto Tri
Abstract: Phenol is one of the most dangerous ingredients in industrial wastewater, which has acute toxicity and is difficult to degrade in the environment. Therefore, Ozone-Plasma Hybrid Reactor (RHOP) is an effective phenol waste treatment used to test the performance of the treatment of synthetic phenolic compounds. Its working principle is based on the combination of ozonation reaction in the liquid plasma field of the reactor. Ozone as a reagent is produced by the ozonator, which is fed into the RHOP by mixing it with the liquid phase feed in the injector to enable the intensive the reaction of the two-phase mixture react. Furthermore, the two-phase mixture intensifies hydroxyl radicals when the liquid phase is in alkaline condition and continuously exposed in plasma. The results obtained from the performance test carried out on several wastes with high concentrations, showed that the system needed improvement. The improvements were made by changing the reactor system to Dielectric Barrier Discharge (DBD) plasma with wire cylinder configuration, to degrade synthetic waste containing phenolic compounds through active species formed in the reactor. This process has a high oxidation potential and decomposes various organic pollutants in waste. Furthermore, the ozonation technique was applied to the DBD reactor with the aim of increasing the amount of ozone and OH radicals, therefore maximizing the phenol degradation process.